MENGKOMPARASIKAN POTENSI IKAN LOW-EKONOMIS (Johnius Spp ; Ilisha elongata) DAN IKAN HIGH-EKONOMIS (Siganus javus ; Caesio cunning) DENGAN ANALISA PROTEINISASI - Salim, Gazali (Jurnal Harpodon Borneo, 2011)
Indonesia is a country that is famous archipelago and the maritime countries which have a sea-based maritime wider than the mainland. Tarakan Island is a tropical region surrounded by the ocean with a very large sea of potential, especially marine resources. The purpose of this study is comparation the low-economical of fish (Johnius Spp and Ilisha elongata) and high-economical of fish (Siganus javus and Caesio cunning) by analyzing the proteins using the weight of wet and dry weight. The method used in this research using descriptive research method. Laboratory analysis using Kjehdahl. The results of fish wet weight test low-lives of fish Ilisha elongata (33.07%) and fish Johnius Spp (16.59%) while the high-economic fish species namely fish Caesio cunning (30.86%) and fish Siganus javus (18.53%). Test dry weight of the fish lives of low-species Ilisha elongata (77.46%) and fish species Johnius Spp (72,73%), whereas the high-economical of fish from fish species Caesio cunning (77.12%) and from fish species Siganus javus (69.19%). Keywords: Comparation, The low and high-economical of fish, Analysis of Protein